Characteristics of Ombudsman Institution in Indonesia Compared with Ombudsman Institution in Sweden, United Kingdom, France, and the Netherlands - Galang Asmara (Faculty of Law, Universitas Padjadjaran, 2016)
Indonesia, as a democratic state of law, performs state management based on the principle of rule of law and the principle of democratic state. One aspect of the implementation of the rule of law and democracy is the provision of legal protection for the public and their parcipation in the public administration, including supervision on the government. In order to achieve this, an Ombudsman institution was established by Indonesian Government in 2000. This institution is intended as a public supervision agency to improve the protection of the rights of the public in obtaining public services, justice, and prosperity. There are currently over one hundred countries in the world with Ombudsman institutions as their government supervision. Every ombudsman institutions have their own unique traits, which is also the case with the Ombudsman institution in Indonesia. This paper discusses the characteristics of the Ombudsman institution in Indonesia and its comparison with some of the Ombudsman institutions of other countries such as Sweden where the Ombudsman originated, the Netherlands, the United Kingdom, and France. The writer chooses ombudsman instuons of those countries for their big influence in shaping the Ombudsman models that exist todayKarakteristik Lembaga Ombudsman di Indonesia Dibandingkan dengan Lembaga Ombudsman Swedia, Inggris, Perancis, dan BelandaAbstrakIndonesia sebagai negara hukum yang demokrasi menghendaki agar penyelenggaraan negara didasarkan pada prinsip rule of law dan prinsip negara demokratis. Salah satu aspek dari pelaksanaan negara hukum yang demokratis tersebut adalah adanya perlindungan hukum bagi masyarakat serta partisipasi masyarakat dalam penyelenggaraan negara termasuk dalam rangka pengawasan pelaksanaan pemerintahan. Untuk mencapai hal tersebut Pemerintah Indonesia sejak tahun 2000 telah membentuk lembaga Ombudsman. Lembaga ini dimaksudkan sebagai lembaga pengawasan publik untuk meningkatkan perlindungan hak-hak masyarakat guna mendapatkan keadilan dan kesejahteraan yang lebih baik. Saat ini ada lebih dari seratus negara di dunia telah memiliki lembaga ombudsman sebagai lembaga pengawasan pemerintahan dengan karakteristik atau ciri-ciri tersendiri. Makalah ini membahas karakteristik lembaga Ombudsman di Indonesia dibandingan dengan beberapa lembaga Ombudsman di negara-negara lain yaitu dengan Swedia sebagai negara asal dari Ombudsman, Inggris, dan Perancis. Lembaga ombudsman di beberapa negara tersebut dipilih karena lembaga ombudsman tersebut sangat mempengaruhi model Ombudsman yang ada di dunia saat ini. DOI: https://doi.org/10.22304/pjih.v3n1.a3